A DYNAMIC SIMULATION MODEL FOR OPTIMAL DEEP-LEVEL MINE COOLING MANAGEMENT AND OPERATIONAL DECISION-MAKING FOR ESKOM’S LOAD CURTAILMENT - Sithole, Shamy Manchala; Gous, Andries; Schutte, Corne (The South African Journal of Industrial Engineering, 2023)
The South African mining sector depends on intensive energy usage to extract minerals. Most of this energy is used to enhance underground working conditions through cooling. Electricity costs have been on the rise, reducing the profitability of mines. Mines must invest in management systems that optimise energy usage while maintaining underground conditions. Dynamic simulation models are critical for systems analysis, optimal management, and improved decision-making. This paper presents an integrated dynamic simulation model for deep-level mine cooling systems. The model was developed using Process ToolBox simulation software, and a Mean Average Percentage Error of 3.53% was achieved. The impact of load curtailment on underground services was simulated. Eight working areas exceeded the legal limit of 32.5 °C, and the steady state simulation underestimated the impact, as only three working areas were affected. The simulation was sensitive to the ambient conditions; high temperatures were noted in the working areas when the ambient temperatures peaked.